Factor structure and invariance of the scale to measure teaching performance in the area of social sciences - Henríquez, Patricio Sebastián; Pérez-Morán, Juan Carlos; del Cid García, Carlos Javier; Zamora, Jesús Enrique (Frontiers in Education, 2023)
The use of scales to evaluate teaching from the students' perspective is a method frequently used in educational systems around the world. The objective of this study is to analyze the factorial structure of the Teaching Performance Evaluation Scale (EEDDocente, by acronyms in Spanish) designed with the purpose of providing information that favors decision-making based on evidence for the improvement of teaching in the area of Social Sciences, as well as measuring the invariance by School stage and Educational Program. The sample consisted of 1,849 students of the Bachelor's Degrees in Law, Psychology, Accounting, Administration, Education Sciences, Communication Sciences, Computer Science and Sociology of the School of Social and Administrative Sciences (FCAyS) of the Autonomous University of Baja California, Mexico. Based on a three-factor model that meets the fit and quality criteria, a Multi-group Confirmatory Factor Analysis (MGCFA) was performed to measure the invariance of the EEDDocente by School stage and Educational program. It is concluded that the three-factor model can be used to measure, from the students' perspective, the performance of teachers in the Area of Social Sciences. Likewise, it is concluded that the invariance of the simultaneous measurement is achieved, providing evidence to perform mean difference analysis between the different Educational programs. This is a provisional file, not the final typeset article Around the world, accountability and the growing demand to ensure the improvement of learning of future professionals graduating from universities has placed the evaluation of teaching performance as the dominant axis of educational policies (Liebowitz, 2022;Vaillant, 2016). However, there is a growing interest in the methodological aspects, techniques and instruments for collecting information (questionnaires, attitude scales, interviews, focus groups, classroom observation), and the subjects (students, teachers, managers, external experts) best suited to obtain reliable, valid,